Oxygen/sulphur self-doped tunnel-like porous carbon from yellow bamboo for advanced supercapacitor applications - Taer, Erman; Yanti, Novi; Putri, Rahma Lia; Apriwandi, Apriwandi; Martin, Awaludin; Julnaidi, Julnaidi; Chitraningrum, Nidya; Fudholi, Ahmad; Taslim, Rika (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The 3D hierarchical pore structure with tunnel-like pores is essential to the performance of porous activated carbon (AC) materials used in symmetric supercapacitors. This study aimed to effect of adding (0.3, 0.5, and 0.7) M KOH reagent and heat treatment on the formation of 3D porous, tunnel-like AC derived from yellow bamboo (YB) through N2-CO2 pyrolysis at 850 °C. The AC produced had a high concentration of nanopores, becoming a valuable storage medium with favorable physical-electrochemical properties. The results showed that 0.5-YBAC had the best physical and electrochemical properties, with a carbon purity, 89.16%, micro crystallinity of 7.374 Å, and excellent amorphous porosity. Furthermore, 3D hierarchical pore structure, enriched naturally occurring heteroatoms, dopant of oxygen (10.14%) and sulfur (0.10%). A maximum surface area of 421.99 m² g⁻¹, along with a dominant combination of micro-mesopores. The electrochemical performance test of the 0.5-YBAC electrode showed a Csp of 214 F g⁻¹, with Esp 24.7 Wh kg⁻¹ and Psp 19.2 W kg⁻¹. In conclusion, this study showed the potential of YB stems to enhance the development of supercapacitors, offering superior porosity characteristics for efficient energy storage applications.